(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The learning interest of students from the results of observations before conducting the research was categorized as less than good, which was 45.07%. This classroom action research aims to improve the learning interest of Class VIII students of SMP Negeri 35 Palembang using the Problem-Based Learning (PBL) learning model with a cultural context in Pjok learning. This research was conducted in 2 cycles using the Kemmis & Mc. The Taggart model has four stages in each cycle, namely planning, implementation, observation and reflection. The subjects of the study were 24 Class VIII students of SMP Negeri 35 Palembang, and the object of the study was the learning interest of students. The data analysis technique using quantitative descriptive methods obtained that the learning interest of students from the results of observations in cycle I was 61.02% categorized as sufficient, and increased to 63.5% categorized as good in cycle II. Based on the results of the questionnaire, the average score of student learning interest in cycle I was 66.11% categorized as sufficient and increased to 79.05% categorized as good, in cycle II. Based on the research results, it can be concluded that the Problem-Based Learning (PBL) learning model with a cultural context can increase the learning interest of Class VIII students of SMP Negeri 35 Palembang in Physical Education learning.